Efektivitas Penggunaan Aplikasi Sirancak dalam Pelayanan Disdukcapil Kota Padang - Dina Nirmala; Syamsir Syamsir; Ayu Zulmi Amanda Pratama; Ari Kurnianto; Alifa Fairuz Shabira; Ade Firman (Ranah Research : Journal of Multidisciplinary Research and Development, 2023)
This e-Government plays an active role in distributing government services to the community or the government works with the private sector and the community through technology to realize public policies and services. One of the government's innovations. The Padang City Population and Civil Registration Service is one of the government agencies that initiated digital-based service innovation, namely in the form of creating a service-based application related to civil registration called Sirancak. The method used in this research is a descriptive qualitative approach by collecting data through direct observation in the field. The aim of the research was to determine the effectiveness of using the Sirancak application in Padang City Dukcapil Disdukcapil services. With the Sirancak application, applicants for population documents can submit their applications and monitor the processing process anytime and anywhere via smartphone, without needing to come to the office. The Sirancak application is also useful for increasing the accuracy and speed of the population data verification process. The Sirancak application is a means of monitoring employee performance and evaluating Disdukcapil services. Based on a Sirancak user survey, as many as 72% of respondents stated that this application really helps save time and costs in processing documents. However, there are obstacles in implementing the Sirancak application, such as the community's low level of technological literacy, technical problems, and attention to data security that need to continue to be considered and improved.